The Influence of Humour on Creative Thinking - Wong, Hong Cheng (1998)
This study was carried out with the firm belief that everyone is born creative, has the capacity to be creative and can be induced to become more creative. Children at tender years show that they are creative until they entered school. The education process and our adult experience have taught us the "habit" of uncreative thinking. Infact, fun and humour have always been perceived as the opposite of work. As such this study tries to uncover the positive effect of humour, specifically how it influences creative thinking. With this in mind, the research is carried out using the nonequivalent control group design where 2 classrooms were selected intact and the Torrance Test of Creative Thinking: Figural Fonn (TTCT) was administered. The score is believed to be an indication of the subject's creative thinking ability. Results of the analysis of data and the interpretations made are based on the t-test analysis. The findings show that (1) humour significantly influences creative thinking, that there is a significant difference between the experimental and control groups; (2),the control group exhibits high post test score on creative thinking, significant even at alpha 0.01, possibly due to the subject's familiarity with the pre-test; and (3) the experiment group, however, showed a higher mean score in their creative thinking. In conclusion, this study indicates that humour significantly influences creative thinking. Having a good laugh and sharing a few jokes does make a difference in their creative thinking, hence making them more creative.